Existence of traversable wormholes in the spherical stellar systems - Övgün, Ali; Halilsoy, Mustafa (Springer, 2016)
Potentiality of the presence of traversable wormholes in the outer/inner regions of the halos of galaxies, situated on the Navarro-Frenk-White (NFW) density profile and Universal Rotation Curve (URC) dark matter models have been investigated recently. Since this covers our own galaxy also as a possible home for traversable wormholes it prompts us to further the subject by considering alternative density distributions. From this token herein we make use of the Einasto model to describe the density profiles for the same purpose. Our choice for the latter is based on the fact that theoretical dark matter halos produced in computer simulations are best described by such a profile. For technical reasons we trim the number of parameters in the Einasto profile to a possible minimum. Based on such a model it is shown that traversable wormholes in the outer regions of spiral galaxies are possible while the inner part regions prohibit such formations.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: wormholes; Milky Way; spherical stellar systems; galaxies; dark matter; Einasto dark matter profile